Nan's Stories - Rangiwai, Byron (Te Kaharoa, 2021)
This paper explores some of the many stories that my grandmother, Rēpora Marion Brown—Nan, told me when growing up and throughout my adult life. Nan was born at Waiōhau in 1940 and died at her home at Murupara in 2017. Nan was married to Papa— Edward Tapuirikawa Brown. Nan and Papa lived on Kōwhai Avenue in Murupara. Nan’s parents were Koro Ted (Hāpurona Edward (Ted) Maki Nātana) and Nanny Pare (Pare Koekoeā Rikiriki). Koro Ted and Nanny Pare lived around the corner from her on Miro Drive. My sister and I were raised on the same street as my great-grandparents, just six or seven houses away. I could see Koro Ted’s house—located on a slight hill—from my bedroom window.